Study of clinical and laboratory profile of patients with reactive arthritis in a tertiary healthcare center - Harsh Jain; Shraddha More; Milind Nadkar; Mulkalwar, Alhad; Hunaid Haider; Aman Goyal (Asian Journal of Medical Sciences, 2022)
Background: Reactive arthritis (ReA) is a spondyloarthropathic disorder characterized by joint pain and swelling triggered by an infection in another part of the body – most often the intestines, genitals, or urinary tract. This condition usually targets the knees, ankles, and feet. The present study was conducted to study the clinical, microbiological, and laboratory profile of patients with ReA and to determine the outcomes over a duration of 3 months. Aims and Objectives: This study aimed to assess the clinical and laboratory profile of patients with ReA in a tertiary healthcare center. Materials and Methods: This was a prospective analytical study undertaken in the Rheumatology Out Patient Department of a tertiary care center. The study involved 73 participants and was completed over a duration of 18 months. Results: Majority of the subjects belonged to the age group of 18–25 years (54.79%), followed by 26–35 years (23.29%) and 36–45 years (10.96%). The mean age of the study subjects was 28.71 ± 10.72 years (median age –25 years). Most of the patients were male (82.19%). While majority of the subjects showed improvement with Non Steroidal Anti-inflammatory Drugs (NSAIDs) (80.82%), steroids were used among 12.33% subjects, sulfasalazine was used among 15.07%, and methotrexate among 1.37% of the study subjects. Conclusion: Statistically significant association was found between HLA B27 positivity and DAREA score, presence of sacroiliitis and extra-articular manifestation. NSAIDs remain the first line agents for patients with ReA. However, high baseline DAREA and ESR of more than 30 is associated with poor response to NSAIDs.